Effect of Silicon Fertilization on Growth, Yield, and Nutrient Uptake of Rice. Issue 3 (4th February 2016) - Pati, Sajal; Pal, Biplab; Badole, Shrikant; Hazra, Gora Chand; Mandal, Biswapati
ABSTRACT: A field experiment was conducted to study the effect of silicon (diatomaceous earth, DE) fertilization on growth, yield, and nutrient uptake of rice during the kharif season of 2012 and 2013 in the new alluvial zone of West Bengal, India. Results showed that application of silicon significantly increased grain and straw yield as well as yield-attributing parameters such as plant height (cm), number of tillers m −2, number of panicle m −2, and 1000-grain weight (g) of rice. The greatest grain and straw yields were observed in the treatment T6 (DE at 600 kg ha −1 in combination with standard fertilizer practice (SFP). The concentration and uptake of silicon, nitrogen (N), phosphorus (P), and potassium (K) in grain and straw were also greater under this treatment compared to others. It was concluded that application of DE at 600 kg ha −1 along with SFP resulted increased grain, straw, and uptake of NPK.